(untitled) (Orfeu, 2019)
This study aims to present aspects of the research project, which is being developed in the Master’s Program in Music (Proemus) of the Federal University of the State of Rio de Janeiro (Unirio). After creating categories of the pedagogical production of Brazilian guitarists (Zanon, 2006), we approached aspects about the elaboration of arrangements for collective musical study of the instrument. Finally, it presents a guitar arrangement for a Brazilian song “O cravo brigou com a rosa”, by using the fundamental aspects addressed by the text. From a theoretical point of view, we discuss France; Swanwick (2002) proposing an instrumental performance study that contemplates creativity, expressiveness and consistency over style.